Analisis Kelayakan Usaha Chicken Rice Bowl pada Perusahaan XYZ - Muhammad Faris Aulia; Raditya Seivel Baldan; Aisha Kurnia Ardiningrun; Alya Aisyah; Dennis Himawan; Veralianita Br Sebayang; Thoifatul Munawwaroh (INDO PUBLISHING, 2026)
This study aims to analyze the financial and non-financial feasibility of the